(untitled) (South East Asia Journal of Public Health, 2017)
Diabetes is a global health burden and threat that needs proper managements. Glycosylated hemoglobin (HbA1c) is an important marker, both in the diagnosis and treatment of diabetes. The purpose of the study was to demonstrate the influence of ethnicity on HbA1c in relation to fasting plasma glucose (FPG), by observation among newly diagnosed type 2 diabetics in Arab population, with a view to speculate comparison with other population groups in order to make a more rationale management plan of diabetes for different ethnic groups. This cross sectional study was performed amongst 573 newly diagnosed, untreated type 2 diabetic subjects attending the outpatient department (OPD) of Al-Qunfudah General Hospital Diabetic centre, in the Kingdom of Saudi Arabia (KSA) from June 2010 to April 2013. Data were collect by face to face interview using pre-tested questionnaire. Height, weight, body mass index (BMI), blood-pressure, fasting and post-prandial venous plasma glucose, HbA1c and serum creatinine were measured. Patients receiving any treatment for diabetes, suffering from Type 1 Diabetes Mellitus (T1DM), having ketonuria ?2+, pregnant and patients of hemolytic anemia were excluded from the study. Sensitivity, specificity and the area under the Receiver Operating Characteristic (ROC) Curve for HbA1c using different cut-off values were calculated using venous FPG considering gold standard. The analysis was done by computer using SPSS version 22.0. Mean fasting plasma glucose was 227.9±81.45mg/dl and mean HbA1c was 9.79±2.22%, 269 patients (47%) had HbA1c >10%, much above ?6.5%, cutoff determined by American Diabetic association (ADA). For diagnosing diabetes, the optional cut-off for HbA1c was 7.9%, with sensitivity of 83.6%, specificity of 87.8%, positive predictive value of 98.6%, and negative predictive value of 33.3%. These characterizations would not only accord to construct more tactical initiative for comparison but also instigate the rationale to individualize HbA1c on ethnic basis for diabetes management protocols. South East Asia Journal of Public Health Vol.6(2) 2016: 42-47